Analysis and Design of Bumdes Applications Using the Waterfall Method - Fajar Akbar Zulmi; Surizar Rahmi Danur; David JM. Sembiring (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
With the existence of Bumdes, it is hoped that it will further move the wheels of the economy and contribute to Original Village Income (PaDes) so that it will have an impact on increasing the rate of village development and improving services to villages. Leading to a more prosperous standard of living for the people of Sungai Ular Village. The BUMDes application in Sungai Ular Village can help Sungai Ular Village in terms of promoting online-based businesses, can make it easier for the community to submit applications for savings and loans, can find out the financial income of BUMDes businesses, and can make it easier to prepare financial reports for BUMDes Sungai Ular, so the design of this application helps resolve existing problems. REFERENCES Faqih, A. R., & Widya, A. A. (2023). Implementasi Aplikasi E-Ticket pada Bumdes Desa Sumbermulyo Kec. Jogoroto Kab. Jombang sebagai Solusi Digitalisasi Pengelolaan Tiket. Jurnal Sistem Informasi, Teknik Informatika Dan Teknologi Pendidikan, 2(2), 49–54. https://doi.org/10.55338/justikpen.v2i2.30 Hikam, M. A., Syauqi, A., & Nabyla, F. (2021). Sistem Informasi Pembayaran Air Pamsimas Bumdes Mendala Jaya Berbasis Android. 2(2). Muhammad Khovivul Anam, Sopingi, & Wijiyanto. (2024). Transformasi Digital Keuangan BUMDes Mata Bangsa Desa Wisata Rotan Trangsan. JEKIN - Jurnal Teknik Informatika, 4(3), 420–430. https://doi.org/10.58794/jekin.v4i3.732 Nafian, K., Irwansyah, M. A., & Sukamto, A. S. (2023). Aplikasi E-commerce Badan Usaha Milik Desa (BUMdes) Berbasis Website. Jurnal Riset Sains Dan Teknologi Informatika, 1(2). Permana, A. A., Agustriawan, D., Johan, M. E., Fianty, M. I., Sanjaya, S. A., Sutomo, R., Istiono, W., Pomalingo, S., Wiratama, J., Fernando, E., Faza, A., & Waworuntu, A. (2023). Software Development Life Cycle. In Introduction to Software Testing (Pertama). EUREKA MEDIA AKSARA. https://doi.org/10.1007/978-1-4842-9514-4_3 Ramadhani, M. M., Hasbi, I., Riyanto, E., Praditasari, W. A., Purwaningrum, J., & Muzid, S. (2022). Teknologi pengembangan (E. Damayanti, Ed.; Pertama). Widina Bhakti Persada Bandung. Setiawan, T., Suryopratomo, A., Yudha, M. F., & Maulana, M. I. (2022). Rancang Bangun Sistem Informasi Media Pembelajaran Interaktif Bahasa Inggris Berbasis Web. Jurnal Accounting Information System, 5(2). Sukamto, R. A. (2022). Analisis dan desain perangkat lunak. Informatika. Usnaini, M., Yasin, V., & Sianipar, A. Z. (2021). Perancangan sistem informasi inventarisasi aset berbasis web menggunakan metode waterfall. Jurnal Manajemen Informatika Jayakarta, 1(1). Waruwu, T. T., & Ridho, F. (2024). Perancangan Aplikasi Informasi Keuangan BUMDes Berbasis Web Di Desa Sitolu’ewali Nias Barat. Jurnal Ilmiah  ILKOMINFO - Ilmu Komputer & Informatika, 7(1), 25–32. https://doi.org/10.47324/ilkominfo.v7i1.218 Yulianti, F. (2021). ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA BUMDES DI DESA SEBERANG CENGAR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI. Jurnal Perencanaan, Sains, Teknologi, Dan Komputer (JuPerSaTek), 4(1). Zalukhu, A., Swingly, P., & Darma, D. (2023). Perangkat Lunak Aplikasi Pembelajaran Flowchart. Jurnal Teknologi, Informasi Dan Industri, 4(1), 61–70.